IMPLEMENTASI PENCATATAN KEUANGAN PADA PENGUSAHA MIKRO-KECIL DI KECAMATAN MRANGGEN-DEMAK (Students' Journal of Accounting and Banking, 2014)
The research aims to describe on how big and how many of laundry service and motorcycle wash service entrepreuners who comprehend and implementing the finance recording that appropriate with the Finance Accounting Standard. The purpose of the research are: 1) To recite the comprehension of the Micro-Small entrepreuners about finance recording on the business, 2) To recite whether the Micro-Small entrepreuner in Mranggen subdistrict of Demak are implementing or coducting the finance recording from business transaction or not. From this research , we found there are 31 laundry service and 79 motorcycle wash in Mranggen Subdistrick of Demak. The analysis tool of the research is statistic Descriptive. Result of the research is on the from of precentage which later described for easy to be understood. The respondents confessed that they are less comprehend with the finance recording of their business. There is 45% respondends who are less comprehend, 26% are comprehend about the finance recording and thr rest or 29% of the are barely comprehend about the finance recording. The number of recpondents who are less and barely comprehend about the finance recording have the limitation of education, most of them are only graduated from elementary school. The diffilculty of implementating the finance recording are 47% of the responding said that they are having diffulculty in implementating the record, 34% said it is very difficult for them to implement it, 18% they are not having any diffulculties in implement it, and 1% said it is not difficult in implementing the finance recording of this business. Keywords: implementation, finacial accounting, and micro service entrepreneur